A First Step in the Co‐Production of a Climate Resilience Research Agenda for the Philadelphia Region - A. Kavathekar; K. Tangtrakul; N. Pearl; D. Bader; J. Britton; S. Chapman; R. Graff; M. Granieri; H. Johnson; R. Johnson; C. Linn; M. Owen; et al. (Community Science)
Abstract The Philadelphia Region is threatened by anthropogenic climate change, with frontline communities facing disproportionate adverse impacts. To be effective, regional plans for climate resilience need to respond to diverse stakeholder needs, with research and information gathering critical to governance and decision‐making. The Climate Resilience Research Agenda (CRRA) is a co‐produced preliminary list of research activities that, if undertaken, could help to make the Philadelphia region more resilient to climate change. The CRRA process engaged over 100 individuals from over 60 organizations and entities across the region, collaboratively producing key research topics across four working groups: 1. Regional Climate Change and Cascading Hazards, 2. Health and Environmental Vulnerability, 3. Built Environment and Infrastructure System Resilience, and Decarbonization/Electrification of the Energy Sector, and 4. Regional Climate Governance and Adaptive Management. Research topics spanned working groups, and connections between topics highlighted the interconnectedness of climate challenges facing the Philadelphia region. In future project phases, the planning team will iterate and improve the recommendations with feedback from the participants from this process to continue important conversations regarding climate resilience within the region.